Perbedaan Kosakata Bahasa Banjar Desa Pabaungan dengan Banjarmasin Kota - Muhammad Irfan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The vocabulary of the Banjar Pabaungan language is slightly different from most of the Hulu languages ​​in South Kalimantan. Differences in vocabulary in the Banjar Pabaungan language are an obstacle for people to communicate with people outside the region. This research aims to enrich knowledge of regional languages ​​that are not widely known to the public. This research uses qualitative methods from interviews, asking questions, documentation, and interacting with the researcher's parents as research subjects. Researchers also use comparative methods to compare two or more languages ​​that originate from a common ancestor. Samples of kakarik, kalamari, and sabura vocabulary were obtained. The vocabulary of kakarik comes from the Bakumpai language which means broom made from dried coconut tree leaf sticks. The word kalamari comes from the Bukit language, meaning dusk. The word sabura is the name of a boat propeller engine called jukung in Banjar language. The Banjar Pabaungan language shows a variety of vocabulary that reflects the cultural identity of the local community. Research on vocabulary in the Banjar Pabaungan language shows that there are phonological variations. By understanding and using regional language vocabulary, we can strengthen cultural identity and improve communication between communities.